2021
DOI: 10.1021/acsomega.1c05441
|View full text |Cite
|
Sign up to set email alerts
|

Mn-Doped Quinary Ag–In–Ga–Zn–S Quantum Dots for Dual-Modal Imaging

Abstract: Doping of transition metals within a semiconductor quantum dot (QD) has a high impact on the optical and magnetic properties of the QD. In this study, we report the synthesis of Mn2+-doped Ag–In–Ga–Zn–S (Mn:AIGZS) QDs via thermolysis of a dithiocarbamate complex of Ag+, In3+, Ga3+, and Zn2+ and of Mn­(stearate)2 in oleylamine. The influence of the Mn2+ loading on the photoluminescence (PL) and magnetic properties of the dots are investigated. Mn:AIGZS QDs exhibit a diameter of ca. 2 nm, a high PL quantum yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Although all aforementioned papers focused on the development of Mn-doped NCs toward achieving the desired optical features as discussed in the Introduction, it should be noted that there are many studies using Mn doping to tune the NC luminescence in a wide-wavelength range (from yellow to red to NIR) or to achieve NCs with double emission peaks covering green to red for the application of photovoltaic devices (e.g., LEDs). Although the exact luminescence mechanisms still need to be investigated further, the Mn–Mn coupling and interaction between Mn and host NCs still can be applied to explain unique luminescence properties in these studies, as discussed by many researchers in their own studies. Generally, it was observed that Mn-doped NCs with emission color tuning presented short lifetimes in the range of several microseconds to tens or hundreds of microseconds.…”
Section: Synthesis and Luminescence Mechanism Of Mn-doped Ncsmentioning
confidence: 99%
“…Although all aforementioned papers focused on the development of Mn-doped NCs toward achieving the desired optical features as discussed in the Introduction, it should be noted that there are many studies using Mn doping to tune the NC luminescence in a wide-wavelength range (from yellow to red to NIR) or to achieve NCs with double emission peaks covering green to red for the application of photovoltaic devices (e.g., LEDs). Although the exact luminescence mechanisms still need to be investigated further, the Mn–Mn coupling and interaction between Mn and host NCs still can be applied to explain unique luminescence properties in these studies, as discussed by many researchers in their own studies. Generally, it was observed that Mn-doped NCs with emission color tuning presented short lifetimes in the range of several microseconds to tens or hundreds of microseconds.…”
Section: Synthesis and Luminescence Mechanism Of Mn-doped Ncsmentioning
confidence: 99%
“…2i, l ). The hysteresis curve of VSM results and the paramagnetic properties of QD and QD@MSN were clearly confirmed with their increased magnetization (Ms) by high magnetic field 44 , 45 . In order to confirm that Gd and Au content was sufficient to produce contrast in an MR and CT image, the same serial concentrations of nanoparticles were assessed (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Accordingly, QDs have been proposed to increase the resolution of these imaging techniques. 83 In other words, bioimaging by QDs is based on the identification of the specific biomarkers of cancer cells and is divided into in-vitro and in-vivo categories. In in-vitro bioimaging, numerous studies have been considered to develop the use of QDs to image the cancer cells of melanoma, ovary, breast, pancreatic, glioblastoma, ovarian epidermoid, lung, hepatocellular, and adenocarcinoma.…”
Section: Bioimaging Of Cancer Cellsmentioning
confidence: 99%